LEGAL IMMUNITY IN CIVIL PROCEEDINGS: CURRENT CHALLENGES - Diduk, Alla; Lytvyn, Stepan (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of this article is to study the current problematic issues related to legal immunity in civil proceedings. To this end, the author analyzes the concepts of "immunity", "legal immunity", "procedural immunity", "attorney’s immunity, witness immunity, court immunity in civil proceedings", as well as external and internal elements of immunity. The author also analyzes the peculiarities of the legal regime of the parties to court proceedings and their practical significance. The methodological basis of the study is general scientific and special methods of scientific cognition. The use of these methods made it possible to analyze legal immunity in civil proceedings and to describe the problems of its legal regime. Results: procedural immunity of an attorney-at-law, an expert, and a judge is their protection from the influence of external and internal factors of public life, both in the course of their professional activities and in their everyday personal life. Discussion: it is necessary to distinguish between external and internal elements of the immunity of an attorney, expert, and judge, which have their own content and therefore affect the external forms of manifestation of independence and inviolability of these persons in connection with their professional activities (for example, for an attorney representing a client in civil proceedings).